Peran Inovasi Teknologi dan Transformasi Digital Dalam Meningkatkan Efisiensi Logistik dan Keberlanjutan Ekonomi Transportasi - Abubakar, Muhammad Masyhur Yunus; Mokodompit, Eliyanti Agus; Usman, Usman (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Bulk cargo transportation plays a strategic role in supporting the national industrial supply chain, particularly for key commodities such as coal, cement, fertilizer, and crude oil. As an archipelagic nation, Indonesia relies heavily on the efficiency of maritime transport to maintain economic stability and logistics resilience. This study aims to analyze the role of technological innovation and digital transformation in improving logistics efficiency and economic sustainability within Indonesia’s bulk cargo transportation sector. The research employs a descriptive–qualitative method with a secondary data analysis approach, utilizing data from the Central Bureau of Statistics (BPS), the Ministry of Transportation, Pelindo, and UNCTAD. The results indicate that the implementation of digital systems such as Inaportnet, Port Operation Control Room (POCR), and Port Community System (PCS) has effectively accelerated logistics flow, reduced operational costs, and enhanced transparency and service accuracy in port operations. Furthermore, digital transformation contributes to reducing carbon emissions and promoting energy efficiency in maritime activities. However, challenges persist, including infrastructure limitations, regional digital disparities, and the low adoption of environmentally friendly technologies across national ports. This study concludes that maritime digitalization is not merely a form of technological modernization but a strategic investment in building an efficient, inclusive, and sustainable national logistics system. The findings are expected to serve as a foundation for formulating public policies to strengthen Indonesia’s maritime economic competitiveness in the digital era.